Genomic assembly, characterization, and quantification of DICER-like gene family in Okra plants under dehydration conditions - Hagar Tarek Elhefnawi; Mohamed Abdel Salam Rashed; Ayman Atta; Rana M. Alshegaihi; Khairiah Mubarak Alwutayd; Diaa Abd El-Moneim; Mahmoud Magdy (PeerJ, 2023)
Background Okra is a plant farmed for its pods, leaves, and stems all of which are edible. It is famous for its ability to tolerate long desiccation periods. It belongs to the Malvaceae family and is a sister species to hibiscus, cotton, and cacao plants. Methods In the current study, okra plants were used as a model to sequence, assemble, and analyze the evolutionary and functional characteristics of the Dicer-like protein gene family (DCL) based on DNAseq and qPCR techniques. Results Four Dicer-like (DCL) single-copy genes of the okra plant Abelmoschus esculentus (L.) Moench (AeDCL) were successfully assembled. The lengths of the AeDCL copies were 8,494, 5,214, 4,731, and 9,329 bp. The detected exons in these samples ranged from a single exon in AeDCL3 to 24 exons in AeDCL4. AeDCLs had five functional domains of two DEAD-like helicase superfamilies, N and C; one Dicer domain; one ribonuclease III domain (a and b); and one double-stranded RNA-binding domain. The PAZ domain was completely annotated only for AeDCL1 and AeDCL3. All AeDCLs were up-regulated under drought conditions, with leaves showing more extensive fold changes than roots. The study focused on a comprehensive genome-wide identification and analysis of the DCL gene family in naturally drought-tolerant okra plants, an orphan crop that can be used as a model for further genomic and transcriptomic studies on drought-tolerance mechanisms in plants.